2017
DOI: 10.1016/j.jpainsymman.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Symptoms and Ventricular Assist Device Implantation

Abstract: Context Ventricular assist devices (VADs) improve quality of life in advanced heart failure (HF) patients, but there are little data exploring psychological symptoms in this population. Objective This study examined the prevalence of psychiatric symptoms and disease over time in VAD patients. Methods This prospective multicenter cohort study enrolled patients immediately before or after VAD implant and followed them up to forty-eight weeks. Depression and anxiety were assessed with PROMIS SF8a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…In contrast, the t-score changed to 44 (±6) and 42 (±9), respectively, 48 weeks after implantation. When plotted on a generalized linear mixed (GLM) model, a decrease overtime signifying improvement with P=0.03 and P<0.001 for depression and anxiety, respectively, was observed [ 18 ]. Another study by Shah et al showed improvement in health-related quality of life (HRQOL), depression, and heart failure symptoms seen in LVAD patients as compared to patients on medical management in the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) 4 group [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the t-score changed to 44 (±6) and 42 (±9), respectively, 48 weeks after implantation. When plotted on a generalized linear mixed (GLM) model, a decrease overtime signifying improvement with P=0.03 and P<0.001 for depression and anxiety, respectively, was observed [ 18 ]. Another study by Shah et al showed improvement in health-related quality of life (HRQOL), depression, and heart failure symptoms seen in LVAD patients as compared to patients on medical management in the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) 4 group [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…-Twenty observational studies of which eight were prospective cohort studies, five retrospective cohort studies, six cross-sectional studies, and one qualitative study [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] -One randomized clinical trial [32] -One systematic review (n=1887) [33] -Four literature reviews [7,[34][35][36] -One practice guideline [1].…”
Section: Reviewmentioning
confidence: 99%
“…Częstość występowania depresji i lęku jest zmienna na różnych etapach leczenia LVAD. Nasila się tuż przed implantacją, ustępuje krótko po niej i ponownie rośnie, jeśli problemy chorego z przystosowaniem się przewyższają umiejętności radzenia sobie [2,33]. U pacjentów ze schyłkową niewydolnością serca objawy depresyjne są najczęściej związane ze stopniem zaawansowania choroby serca, w tym z gorszym funkcjonowaniem fizycznym i gorszym rokowaniem odległym.…”
Section: Okres Pooperacyjnyunclassified
“…Elevated rates of depression, anxiety, and decreased QOL have been identified in posttransplant patients and inconsistently in VAD patients [6][7][8]. However, there is limited evidence as to the effect of other mental health disorders (MHDs) and SUDs.…”
Section: Introductionmentioning
confidence: 99%